Engaging in Corruption: The Influence of Cultural Values and Contagion Effects at the Micro Level - Wang-Sheng Lee; Cahit Guven (Institute for the Study of Labor (IZA), 2013)
Previous empirical work on corruption has generally been cross-country in nature and focused on utilizing country-level corruption ratings. By using micro-level data for over 20 European countries that directly measure individual characteristics, corruption experiences, gender roles, trust and values to examine the determinants of corruption, this paper goes beyond the search for associations between various macro factors and perceptions of corruption that is prevalent in the economic literature. One focus of the paper is on how cultural norms such as gender roles and risk preferences influence corruption and whether there are gender differences in the determinants of corruption. In addition, this paper also seeks to determine if there are contagion effects in corruption at the micro level. Using a seemingly unrelated probit approach, this paper provides empirical estimates of how past experiences with corruption affects both how bribery is viewed and the actual act of offering a bribe.
Keywords: K42; O17; 330; risk preference; gender roles; corruption; seemingly unrelated probit